Frequency and temperature dependent electrical and dielectric properties of LaCrO3 and Ir doped LaCrO3 perovskite compounds - Coşkun, M.; Coşkun, F. M.; Durmuş, Zehra; Çağlar, Müjdat; Turut, Abdulmecit; POLAT, ÖZGÜR (Elsevier Science Sa, Po Box 564, 1001 Lausanne, Switzerland, 2018)
Perovskite oxide materials, especially perovskite lanthanum chromium oxide, LaCrO3 (LCO) have taken considerable attention among the scientists due to the changing optical, electrical, dielectric and magnetic properties depending on doping via various elements. In this study, the LCO and iridium (Ir) doped LCO (LaCr1-xIrxO3) (x = 0.10) compounds were synthesized using solid-state reaction method. Scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS) have been employed to study particle morphologies and oxidation states of synthesized powders, respectively. Frequency-depended electrical/dielectric properties of perovskite oxide samples were performed in wide range frequency (1Hz-10 MHz) and temperature (-100 degrees C to +100 degrees C) using dielectric/impedance spectrometer. Electrical measurements have underscored that the dielectric constant of LCO compound dramatically decreased after doped with Ir. Furthermore, it was observed that ac conductivity and capacitance value of LCO decreased while impedance increased after Ir doping due to i) Ir occupation in Cr sites and ii) lattice distortion owing to doping larger ion Ir4+ into smaller Cr3+ ion in the LCO lattice. Finally, overlapping large polaron tunneling (OLPT) and quantum mechanical tunneling (QMT) conduction mechanisms were suggested for LCO while the correlated barrier hopping (CBH) and QMT conduction mechanisms were observed for Ir doped LCO compound. Moreover, the activation energy values have been calculated by employing both f(max) vs. 1/T and sigma(dc) vs. 1/T plots. It has been shown those energy values are in good agreement with each other for LCO and Ir doped LCO samples at various temperature ranges. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: LaCrO3; Ir; Dielectric properties; Conductivity; Impedance spectroscopy; Oxide Fuel-Cells; Impedance Spectroscopy; Optical-Properties; Conductivity; Co; Electroceramics; Nanoparticles; Substitution; Stability; Ceramics